Gnostic Apocalypse and Islam : Qur'an, Exegesis, Messianism and the Literary Origins of the Babi Religion. - Lawson, Todd (Iranian Studies., 2011)
Of the several works on the rise and development of the Babi movement, especially those dealing with the life and work of its founder, Sayyid Ali Muhammad Shirazi, few deal directly with the compelling and complex web of mysticism, theology and philosophy found in his earliest compositions. This book examines the Islamic roots of the Babi religion, (and by extension the later Baha'i faith which developed out of it), through the Qur'anic commentaries of the Bab and sheds light on its relationship to the wider religious milieu and its profound debt to esoteric Islam, especially Shi'ism. Todd Law.